Optimization of Profit-Sharing Financing for the Recovery of MSMEs in Islamic Banks During the Covid-19 Pandemic - Trimulato, Trimulato; Rodoni, Ahmad; Amelia, Erika (CV Widina Media Utama, 2025)
This study aims to analyze the development and optimization of profit-sharing financing by Islamic banks to support MSMEs' recovery during the Covid-19 pandemic. Using a qualitative library research approach, the study collected secondary data from OJK, academic journals, and relevant reports. Descriptive qualitative analysis reveals that while profit-sharing financing slightly declined during the pandemic, it remains a strategic instrument for promoting MSME resilience. Optimizing profit-sharing schemes, such as mudharabah and musyarakah, requires stronger bank-customer partnerships and adaptive financial strategies to support real sector recovery.ABSTRAKPenelitian ini bertujuan untuk menganalisis perkembangan dan optimalisasi pembiayaan bagi hasil oleh bank syariah untuk mendukung pemulihan UMKM selama pandemi Covid-19. Dengan menggunakan pendekatan penelitian kepustakaan kualitatif, studi ini mengumpulkan data sekunder dari OJK, jurnal akademik, dan laporan yang relevan. Analisis kualitatif deskriptif menunjukkan bahwa meskipun pembiayaan bagi hasil sedikit menurun selama pandemi, pembiayaan bagi hasil tetap menjadi instrumen strategis untuk mendorong ketahanan UMKM. Optimalisasi skema bagi hasil, seperti mudharabah dan musyarakah, membutuhkan kemitraan bank-nasabah yang lebih kuat dan strategi keuangan yang adaptif untuk mendukung pemulihan sektor riil.